Multicultural Education Through Material on the Basic Formulation of the Republic of Indonesia as an Effort to Cultivate an Attitude of Tolerance - Oktavia Wahyuni Saputri; Indah Puji Utami; Joko Sayono (Lingeduca: Journal of Language and Education Studies, 2024)
Indonesia is a country that has different cultures, ethnicities, customs, religions, languages, and customs. The existence of multiculturalism in Indonesia is a challenge for the Indonesian people to maintain Indonesian unity. Often conflicts that contain elements of SARA occur in Indonesia, if this continues to occur it will divide Indonesian unity. To reduce SARA conflicts, you can start from an attitude of tolerance which can be learned through material on the basic formulation of the Indonesian state. In this research, the literature review method was used. The research results show that an attitude of tolerance can be instilled through multicultural education in schools through the values in the basic formulation of the Indonesian state.